Tangled Threads: Mentoring within a community of practice - Tarr, Patricia (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
Tangled Threads, a case study of a group of women art educators, examines the nature of mentoring relationships within the context of a professional association. Grounded in literature on community of practice, relational and peer mentoring, and an ethic of care, the study uncovers the complex interconnections between women’s professional and personal lives that serve to create contexts for fluid and diverse mentoring experiences.